2016
DOI: 10.1016/j.jvs.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Microembolization Is Associated With Transient Cognitive Decline in Patients Undergoing Carotid Interventions

Abstract: OBJECTIVE-Carotid interventions are important in helping to reduce the risk of stroke for patients with high-grade carotid artery stenosis; however, incidence of subclinical cerebral microemboli can occur during these procedures. Previously, associations have been found between incidence of microemboli and postoperative decline in memory. We therefore sought to determine whether this decline persisted long-term and to assess changes in other cognitive domains. METHODS-Patientswere prospectively recruited under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
1
14
1
Order By: Relevance
“…All study patients who suffered from mesenteric embolization had undergone advanced time-consuming endovascular procedures, prior to the embolic event, where manipulation of numerous guidewires, sheaths, and stent grafts within atherosclerotic aorta and visceral arteries lined with a thrombus very likely contributed to this adverse outcome. In view of a recent report on carotid interventions where an alarming 85% of all endovascular carotid artery stenting procedures resulted in new microemboli [8], it seems probable that microembolization occurs much more often [9] after complex endovascular aorto-iliac procedures than the reported macroembolization rate of 1.8% in the present study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…All study patients who suffered from mesenteric embolization had undergone advanced time-consuming endovascular procedures, prior to the embolic event, where manipulation of numerous guidewires, sheaths, and stent grafts within atherosclerotic aorta and visceral arteries lined with a thrombus very likely contributed to this adverse outcome. In view of a recent report on carotid interventions where an alarming 85% of all endovascular carotid artery stenting procedures resulted in new microemboli [8], it seems probable that microembolization occurs much more often [9] after complex endovascular aorto-iliac procedures than the reported macroembolization rate of 1.8% in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…Hence, the results of our study, and one previous study, suggest that smoking and renal insufficiency are, indeed, risk factors for mesenteric embolization after aortoiliac procedures [5]. Although diabetes was not found to increase the risk of mesenteric embolization in the present study, microembolism has been reported to be more likely in diabetics after carotid interventions [8].…”
Section: Discussionsupporting
confidence: 50%
“…Seventy-nine studies were excluded for the following reasons: MRI to detect cerebral ischaemia did not include DWI sequences, or DWI was not done in all patients (n = 15); 2236 no DWI was performed before treatment (n = 11); 3747 post-procedural DWI was performed more than seven days after treatment (n = 3); 4850 the number of DWI+ patients or procedures could not be extracted (n = 6); 5156 or information on procedural stroke was lacking or patients with procedural stroke were excluded from the analysis (n = 6). 49,5768 One study was excluded because the analysis was restricted to patients with available six months’ follow-up who constituted less than half of the study population (n = 1). 69 One study was excluded since only pre-selected groups of patients showing micro-embolic signals in transcranial Doppler during CEA were included in the final analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Hitchner et al observed a higher rate of new microemboli after CAS compared to CEA with a signifi cantly related cognitive decline at 30 days. Six months after intervention, an association between emboli and decline could no longer be demonstrated [47]. For CEA, CREST showed a signifi cantly increased rate of periprocedural MI and cranial nerve palsy (2.3 % and 4.7 % vs. 1.1 % and 0.3 % with CAS).…”
Section: Benefi T and Harm From Treatmentmentioning
confidence: 94%